Avian Neo-Sex Chromosomes Reveal Dynamics of Recombination Suppression and W Degeneration. (20th September 2021) - Sigeman, Hanna; Strandh, Maria; Proux-Wéra, Estelle; Kutschera, Verena E; Ponnikas, Suvi; Zhang, Hongkai; Lundberg, Max; Soler, Lucile; Bunikis, Ignas; Tarka, Maja; Hasselquist, Dennis; Nystedt, Björn; et al.
Abstract: How the avian sex chromosomes first evolved from autosomes remains elusive as 100 million years (My) of divergence and degeneration obscure their evolutionary history. The Sylvioidea group of songbirds is interesting for understanding avian sex chromosome evolution because a chromosome fusion event ∼24 Ma formed "neo-sex chromosomes" consisting of an added (new) and an ancestral (old) part. Here, we report the complete female genome (ZW) of one Sylvioidea species, the great reed warbler ( Acrocephalus arundinaceus ). Our long-read assembly shows that the added region has been translocated to both Z and W, and whereas the added-Z has retained its gene order the added-W part has been heavily rearranged. Phylogenetic analyses show that recombination between the homologous added-Z and -W regions continued after the fusion event, and that recombination suppression across this region took several million years to be completed. Moreover, recombination suppression was initiated across multiple positions over the added-Z, which is not consistent with a simple linear progression starting from the fusion point. As expected following recombination suppression, the added-W show signs of degeneration including repeat accumulation and gene loss. Finally, we present evidence for nonrandom maintenance of slowly evolving and dosage-sensitive genes on both ancestral- and added-W, a process causing correlated evolution among orthologous genes across broad taxonomic groups, regardless of sex linkage.